The Role of Digitalization in the Boosting of Global Economy - Jo’rayev Og’abek (Global Scientific Publishing, 2023)
This article talks about foreign experience and innovation in the development of digital economy. In the conditions of today's rapidly developing global economy, the digital economy is at the initial stage of its development, and it will take a few years before the complete transition of our time to the digital information stage
Keywords: digital economy; revolution; humanity; international competition